Analyzing Macro-Nutrient Intake and Nutritional Status of Adolescent Girls in Manado - Veibi Ester Politon; Yulianty Sanggelorang; Nancy S H Malonda (JURNAL BIOS LOGOS, 2024)
The nutritional status is directly influenced by macronutrient intake, with imbalances potentially leading to nutritional issues. This study aimed to analyze the correlation between macronutrient intake and the nutritional status of female students at State Senior High School (SSHS) 9 Manado. Employing an analytic survey with a cross-sectional design, the research was conducted from February to June 2023 at SSHS 9 Manado, involving students from grades X and XI, totaling 100 samples. Research instruments included a 24-hour food recall form, a microtoise for height measurement, and a digital scale for weight measurement. The correlation between variables was tested using the Spearman Rank correlation test. Findings revealed that a majority of respondents exhibited deficits in carbohydrate, protein, and fat intake, despite maintaining a normal nutritional status of 81%. However, statistical analysis indicated no significant relationship between carbohydrate, protein, and fat intake and the nutritional status of female students. Consequently, it was concluded that there was no significant correlation between macronutrient intake and the nutritional status of female students at SSHS 9 Manado.